2019
DOI: 10.4049/jimmunol.1900377
|View full text |Cite
|
Sign up to set email alerts
|

Primary EBV Infection Induces an Acute Wave of Activated Antigen-Specific Cytotoxic CD4+ T Cells

Abstract: Key Points Primary EBV infection drives highly cytotoxic virus-specific CD4 + T cell responses. EBV-specific memory CD4 + T cells are polyfunctional but lack cytotoxic activity. Acute EBV-specific CD4-CTLs differ transcriptionally from classical memory CD4-CTLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 75 publications
(125 reference statements)
4
33
0
Order By: Relevance
“…Normally, this mechanism is compensated by the presence of cytotoxic CD4 + Th cells, which keep these types of infections under control (95). Such Th populations have been associated with MS progression (96) and are also formed after EBV infection, producing high levels of IFN-γ, IL-2, granzyme B, and perforin (97,98). Similarly, EBV-and myelin-reactive Th cells from MS patients produce high levels of IFN-γ and IL-2 (6) and strongly respond to memory B cells presenting myelin peptides (99).…”
Section: B Cells As Inducers Of Pathogenic Memory Th Cellsmentioning
confidence: 99%
“…Normally, this mechanism is compensated by the presence of cytotoxic CD4 + Th cells, which keep these types of infections under control (95). Such Th populations have been associated with MS progression (96) and are also formed after EBV infection, producing high levels of IFN-γ, IL-2, granzyme B, and perforin (97,98). Similarly, EBV-and myelin-reactive Th cells from MS patients produce high levels of IFN-γ and IL-2 (6) and strongly respond to memory B cells presenting myelin peptides (99).…”
Section: B Cells As Inducers Of Pathogenic Memory Th Cellsmentioning
confidence: 99%
“…The functional profile of EBV-specific CD4+ T cells is consistent with Th1-like cells: most express T-bet and the predominant cytokine produced in ex vivo stimulation assays is IFNg. Some cells also produce TNFα and/or IL-2, either in combination with IFNg or alone (41, 42). Early observations of raised perforin expression within the total CD4+ T cells of IM patients suggested that cytotoxic CD4+ T cells are present during primary EBV infection (43).…”
Section: The Ebv-specific T-cell Response During Symptomatic Primary mentioning
confidence: 99%
“…Recent ex vivo HLA class II tetramer analysis has now shown that in fact the majority of activated EBV-specific CD4+ T cells express both perforin and granzyme B. Importantly, these cytotoxic proteins were not detected in co-existing influenza A-specific memory CD4+ T cells demonstrating that such expression was not due to non-specific bystander activation (42). Testing with EBV peptides has shown that some EBV-specific CD4+ T cells upregulate cell surface CD107a indicating degranulation and release of perforin and granzyme is possible (41).…”
Section: The Ebv-specific T-cell Response During Symptomatic Primary mentioning
confidence: 99%
“…In contrast, MHC class II restricted CD4 + T cells recognize a broad range of latent EBV antigens, with EBNA1 specific CD4 + T cells present in every healthy virus carrier [49,50]. All latent EBV antigen specific CD8 + and many CD4 + T cells directly recognize LCLs and can kill them, suggesting protective functions against EBV infection and its pathologies in vivo [51][52][53]. Among these T cell responses, EBNA1 and/or LMP1 and LMP2 specific T cells have been selectively isolated or expanded for adoptive transfer into patients with EBV associated malignancies, resulting in clinical benefits [26,[54][55][56].…”
Section: Antigen Specificity Of Protective T Cell Responses Against Ebvmentioning
confidence: 99%